Enhanced Photoresponse from Phosphorene–Phosphorene‐Suboxide Junction Fashioned by Focused Laser Micromachining. Issue 21 (29th March 2016) - Lu, Junpeng; Carvalho, Alexandra; Wu, Jing; Liu, Hongwei; Tok, Eng Soon; Neto, Antonio H. Castro; Özyilmaz, Barbaros; Sow, Chorng Haur
Abstract : Enhanced photoresponse is obtained from phosphorene–phosphorene‐suboxide. A scanning focused laser beam is employed as a straightforward approach to convert part of a phosphorene film into phosphorene suboxide, creating a functional junction in situ on an optoelectronic device based on phosphorene. As a result, the photoelectrical properties of the optoelectronic device are significantly improved.